Patterns of Relations between Adolescents and Parents and Their Impact on Religious Moderation Attitudes (Case Studies in Bali and Madura) - Sahari, Sahari; Gunawan, Edi; Aisa, Siti; Tohis, Reza Adeputra (IAIN Manado, 2024)
Abstract: This study aims to examine the patterns of relationships between adolescents and parents and their influence on the attitudes toward religious moderation among student adolescents in Bali's multicultural society and Santri adolescents in Madura's religious and homogeneous society. This research employs a quantitative research method with a survey approach. The results indicate that the relationship between parents and adolescent students in Bali and Madura shows a very good pattern, with an average score of 53.88. There are differences in the patterns of relationships between adolescents and parents in Madura and Bali. In Madura, the adolescent-parent relationship demonstrates authoritarian and democratic patterns, while in Bali, it shows permissive and neglectful patterns. The democratic relationship pattern has the highest average value compared to other relationship patterns. Overall, relationship patterns have a significant positive correlation with religious moderation among adolescents in Madura and Bali.Keywords: Relationship Patterns; Adolescents and Parents; Religious Moderation; Multicultural Abstrak: Penelitian ini bertujuan mengkaji pola relasi remaja dan orangtua serta pengaruhnya terhadap sikap moderasi beragama remaja pelajar pada masyarakat Bali yang multikultural dan remaja santri pada masyarakat Madura yang religius dan homogen. Penelitian ini menggunakan metode penelitian kuantitatif dengan pendekatan survei. Hasil penelitian menunjukan bahwa relasi antara orang tua dan remaja pelajar di Bali dan Madura memiliki pola yang sangat baik dengan skor rata-rata 53,88. Terdapat perbedaan pola relasi remaja dan orang tua pada masyarakat Madura dan Bali. Di Madura relasi remaja-orang tua menunjukkan pola otoriter dan demokratis, sedangkan di Bali menunjukan pola permisif dan abai. Pola relasi demokratis memiliki nilai rata-rata paling tinggi dari pola relasi yang lain. Secara keseluruhan pola relasi memiliki hubungan positif yang signifikan dengan moderasi beragama pada remaja di Madura dan Bali.Kata Kunci: Pola Relasi; Remaja dan Orang Tua; Moderasi Beragama; Multikultural